ANALISIS RASIO LIKUIDITAS SEBAGAI ALAT PENILAIAN UNTUK MENGUKUR KINERA KEUANGAN PT PRODIA WIDYAHUSADA TBK PERIODE 2016-2018 - Rina Masitoh Haryadi3, Rintina Desty Oktaviani1 Eka Yudhyani 2 (EKONOMIA, 2021)
ABSTRACTThe Hipotezise of research are 1) Financial Perform analize on likuidity ratio (Quick Ratio) of PT Prodia Widyahusada Tbk on Indonesia Stock Exchange years 2016-2018 increase 2) Financial Perform analize on likuidity ratio (Current Ratio) of PT Prodia Widyahusada Tbk on Indonesia Stock Exchange years 2016- 2018 increase. 3) Financial Perform analize on likuidity ratio (Cash Ratio) of PT Prodia Widyahusada on Indonesia Stock Exchange years 2016-2018 increase 4) Financial Perform analize on Likuidity ratio (Inventory Toward Equity Ratio) of PT Prodia Widyahusada Tbk on Indonesia Stock Exchange years 2016-2018 increase.The results of the financial ratio analysis show that: 1) Financial performance in terms of the Liquidity Ratio (Quick Ratio) of PT Prodia Widyahusada Tbk 2016-2017 has increased so the hypothesis is accepted, 2017- 2018 has decreased, so the hypothesis is rejected. 2) Financial performance in terms of the Liquidity Ratio (Current Ratio) of PT Prodia Widyahusada Tbk in 2016-2017 has increased so the hypothesis is accepted, 2017-2018 has decreased, so the hypothesis is rejected. 3) Financial performance in terms of the Liquidity Ratio (Cash Ratio) of PT Prodia Widyahusada Tbk in 2016-2018 has decreased, so the hypothesis is rejected. 4) Financial performance in terms of the Liquidity Ratio (Inventory toward equity) of PT Prodia Widyahusada Tbk in 2018-2020 has increased, so the hypothesis is accepted.